1986
DOI: 10.1111/j.1095-8649.1986.tb05159.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors influencing the composition of the parasite fauna of the European eel, Anguilla anguilla (L.), in Ireland

Abstract: The parasites of 121 eels from three contrasting sites in the Corrib catchment area, western Ireland, were investigated. Thirteen species, Ergusilus gibbus, Diplosromun gasrerosrei. Diplosrornrtnr spurhaceum. Sphaerosroma branrae. Borhrocephalus claviceps. Proreocephalus mrrc~rocepholus. Cavrullunus lacusiris, Cucullanus rruriae, Parayuimperia renerrima, Ruphidascaris acus. Acunrhocephalus clavulu, Aconlhocephulus lucii and Pomphorhvnchus luevis, were recorded. Two species, P. macrocephalus and P . renerrima, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 14 publications
5
34
1
Order By: Relevance
“…Therefore, the study of age, as well as length, has become an important tool to understand the relationships between parasites and their hosts. Lawrence (1970), Muzzall (1980 and Conneely & McCarthy (1986) observed that in addition to age, host sex and flood period also influenced parasite abundance. The action of these factors on the parasite fauna is considerable, mainly for those that have several organisms as intermediate hosts.…”
Section: Sexmentioning
confidence: 97%
“…Therefore, the study of age, as well as length, has become an important tool to understand the relationships between parasites and their hosts. Lawrence (1970), Muzzall (1980 and Conneely & McCarthy (1986) observed that in addition to age, host sex and flood period also influenced parasite abundance. The action of these factors on the parasite fauna is considerable, mainly for those that have several organisms as intermediate hosts.…”
Section: Sexmentioning
confidence: 97%
“…Conneely and McCarthy, 1986;Køie, 1988a;Kennedy, 1993Kennedy, , 1997Schabuss et al, 1997;Kennedy et al, 1998;Sures et al, 1999;Di Cave et al, 2001;Aguilar et al, 2005;Kristmundsson and Helgason, 2007). Investigations on the parasite fauna of European eels in marine habitats (Outeiral et al, 2001(Outeiral et al, , 2002Kristmundsson and Helgason, 2007) are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, there is evidence to suggest that Acanthocephala are more likely than other groups of helminths to exhibit negative interactions with their own and other species, under both field (Chappell, 1969 ;Grey & Hayunga, 1980 ;Kennedy, 1992 ;Vidal-Martinez & Kennedy, 2000) and experimental conditions (Holmes, 1961Holland, 1984Holland, , 1987Bates & Kennedy, 1990, 1991. Secondly, the likelihood of these interactions is increased in Ireland because of the absence of certain definitive hosts (Lyndon & Kennedy, 2001) and the fact that concurrent infections by 2 or more species of Acanthocephala are more commonly observed in aquatic hosts including fish (Kane, 1966 ;Kennedy, 1966 ;Conneely & McCarthy, 1984, 1986Holland & Kennedy, 1998). For example, Kennedy & Moriarty (1987) observed stable populations of Acanthocephalus lucii and Acanthocephalus anguillae in eels over a 3-year period in Lough Derg.…”
Section: Discussionmentioning
confidence: 99%